Subcutaneous implantation of unidirectional self-inflating anisotropic tissue expander has no effect on the physiological parameters and behaviours of horses - Al-Majhali, Saddam Hussein; Khairuddin, Nurul Hayah; Abdul Razak, Intan Shameha; Radzi, Zamri; Rahman, Mohammad Tariqur; Tengku Azizan, Tengku Rinalfi Putra; Sapalo, John Tito; Musa Mayaki, Abubakar (Universiti Putra Malaysia, 2022)
The tissue expansion technique is one of the most important innovations in skin reconstructive surgery in human and veterinary medicine. This study investigated horses’ physiological and behavioural responses to subcutaneous implantation of a unidirectional self-inflating anisotropic tissue expander. The tissue expanders were subcutaneously implanted on six horses at three different locations: the frontal region of the head, the lateral side of the right shoulder, and the dorsomedial part of the cannon region of the right forelimb. Prior to the tissue expander implantation, each horse was clinically examined, and the observed vital parameters and behaviour were recorded as baseline data. For six days post implantations, the horses were clinically examined, implantation sites monitored, and the horse’s behaviour was recorded both during the day by visual observation and at night with a video camera. The results showed that all horses tolerated the subcutaneous gradual skin expansion by implantation of the tissue expanders, and all surgical sites healed without any complications. The implantation of the tissue expanders does not affect the vital parameters or overall horse behaviour either during the day or at night. In conclusion, the subcutaneous implantation of unidirectional anisotropic tissue expanders in horses resulted in successful skin growth with no physiological and psychological discomfort; hence skin expansion is a good option to be considered when pursuing equine skin reconstructive surgery.